Can soy isoflavones plus soy protein change serum levels of interlukin‐6? A systematic review and meta‐analysis of randomized controlled trials. (12th October 2020) - Gholami, Ali; Baradaran, Hamid Reza; Hariri, Mitra
Abstract : In the present review, we aimed to summarize the effect of soy isoflavones plus soy protein on circulating interlukin‐6 (IL‐6) in adult participants. Databases including ISI Web of Science, PubMed, Scopus, Cochrane Library, and clinicaltrials.gov were searched up to 23 March 2020. The mean change from baseline of IL‐6 concentrations and its SD for intervention and comparison groups were used to calculate the effect size. If the heterogeneity test was statistically significant, DerSimonian and Laird random effects model was used. Cochran's Q test and I‐squared statistic were also used to compute the statistical heterogeneity of the intervention's effects. Eighteen studies were known to be eligible for systematic review and 14 studies were selected for meta‐analysis. Our meta‐analysis results indicated a non‐significant effect in serum IL‐6 concentrations compared to the comparison group (WMD = 0.03 pg/ml, 95% CI: −0.06, 0.12; p = .459). In subgroup analysis, based on soy isoflavones dosage, it was observed that this combination could reduce IL‐6 levels in studies that used isoflavones with dose >84 mg/day (WMD = −0.12 pg/ml 95% CI: −0.24, −0.004; p = .042, I 2 = 82.7%) and in articles with a good quality (WMD = −0.15 pg/ml 95% CI: −0.24, −0.05; p = .003, I 2 = 62.3%). Performing well‐designed intervention studies using a high dose of soy isoflavones is recommended to confirm the beneficial effects of soy ingredients on IL‐6.